2023
DOI: 10.3847/1538-3881/acf28e
|View full text |Cite
|
Sign up to set email alerts
|

A Nondetection of Iron in the First High-resolution Emission Study of the Lava Planet 55 Cnc e

Kaitlin C. Rasmussen,
Miles H. Currie,
Celeste Hagee
et al.

Abstract: Close-in lava planets represent an extreme example of terrestrial worlds, but their high temperatures may allow us to probe a diversity of crustal compositions. The brightest and most well-studied of these objects is 55 Cancri e, a nearby super-Earth with a remarkably short 17 hr orbit. However, despite numerous studies, debate remains about the existence and composition of its atmosphere. We present upper limits on the atmospheric pressure of 55 Cnc e derived from high-resolution time-series spectra taken wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Similarly, we expect our wavelength solution to be reliable to ∼100 m s −1 , substantially better than the observed shift. Rasmussen et al (2023) demonstrated that the shift in planetary lines within a science exposure can produce a blueshift of several kilometers per second, though we expect this effect to be minimal given the <1 km s −1 velocity shift between successive spectra in the time series. However, we did not attempt to account for the wavelength dependence or non-Gaussian wings of the NIRSPEC LSF (López et al 2020), potentially leading to a model mismatch in the line shapes that could bias the retrieved velocities.…”
Section: Winds and Circulationmentioning
confidence: 81%
“…Similarly, we expect our wavelength solution to be reliable to ∼100 m s −1 , substantially better than the observed shift. Rasmussen et al (2023) demonstrated that the shift in planetary lines within a science exposure can produce a blueshift of several kilometers per second, though we expect this effect to be minimal given the <1 km s −1 velocity shift between successive spectra in the time series. However, we did not attempt to account for the wavelength dependence or non-Gaussian wings of the NIRSPEC LSF (López et al 2020), potentially leading to a model mismatch in the line shapes that could bias the retrieved velocities.…”
Section: Winds and Circulationmentioning
confidence: 81%
“…Second, the recent chemical detections in K2-18 b with JWST demonstrate both the H 2 -rich nature of such atmospheres and the presence of prominent molecules, above any potential cloud decks, in abundances high enough to be detectable. Third, ground-based high-resolution transit spectroscopy is now a proven technique for detecting chemical signatures in hot Jupiters (Snellen et al 2010;Birkby et al 2013;Brogi et al 2018;Sánchez-López et al 2019), with recent efforts directed toward atmospheres of hot rocky exoplanets (Jindal et al 2020;Rasmussen et al 2023;Ridden-Harper et al 2023). Theoretical studies have demonstrated that the same is also feasible for mini-Neptunes orbiting bright M dwarfs (Gandhi et al 2020;Hood et al 2020).…”
Section: Introductionmentioning
confidence: 99%